A Review of Inter-Civilizational Dialogue: Governmental and Private Initiatives (American Journal of Islam and Society, 2010)
Is interfaith dialogue full of challenges or opportunities? Does itlead somewhere, or is it a never ending circular road? When wedialogue, do we still harbor the notion of converting our dialoguepartners? Analyzing some of the actual work done by governmentsand non-governmental organizations (NGOs), as well asacademics and individuals, may answer these questions. In thisshort article, I will focus on several efforts’ goals, success rate,and what we can learn from their experiences.